The public health benefit and burden of mass drug administration programs in Vietnamese schoolchildren: Impact of mebendazole - Debaveye, Sam; Gonzalez Torres, Claudia Virginia; De Smedt, Delphine; Heirman, Bert; Kavanagh, Shane; Dewulf, Jo (PLOS Neglected Tropical Diseases, 2018)
Background Mass anthelmintic drug administration is recommended in developing countries to address infection by soil-transmitted helminthiases (STH). We quantified the public health benefit of treatment with mebendazole in eight million Vietnamese children aged 5–14 years from 2006 to 2011. This was compared to the environmental impact of the pharmaceutical supply chain of mebendazole, as the resource use and emissions associated with pharmaceutical production can be associated with a public health burden, e.g. through emissions of fine particulate matter. Methodology Through Markov modelling the disability due to STH was quantified for hookworm, Ascaris lumbricoides and Trichuris trichiura. For each worm type, four levels of intensity of infection were included: none, light, medium and heavy. The treatment effect on patients was quantified in Disability-Adjusted Life Years (DALYs). The public health burden induced by the pharmaceutical supply chain of mebendazole was quantified in DALYs through Life Cycle Assessment. Principal findings Compared to ‘no treatment’, the modelled results of five-year treatment averted 116,587 DALYs (68% reduction) for the three worms combined and largely driven by A. lumbricoides. The main change in DALYs occurred in the first year of treatment, after which the results stabilized. The public health burden associated with the pharmaceutical supply chain was 6 DALYs. Conclusions The public health benefit of the Mass Drug Administration (MDA) averted substantially more DALYs than those induced by the pharmaceutical supply chain. These results were verified in a sensitivity analysis. The starting prevalence for each worm was the most sensitive model parameter. This methodology is useful for policymakers interested in a holistic approach towards the public health performance of MDA programs, enveloping both the treatment benefit received by the patient and the public health burden associated with the resource consumption and environmental emissions of the pharmaceutical production and supply chain.